Phonological, morphosyntactic and morphological integration of French loanwords into Jordanian Arabic of Amman - Awwad, Mousa; Hammouri, Hamzeh; Allawzi, Areej (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims at examining how the Jordanian Arabic dialect, particularly that of Amman, integrates French loanwords into its phonology, morphosyntax, and morphology. Methods: The study is carried out based on a corpus that consists of three hundred French loanwords used in the Jordanian dialect. Loanwords and their different forms of integration are identified by comparing their forms in the lending language with their forms in the borrowing language. To examine the morphological and phonological variants of loanwords and their realizations in Jordanian Arabic of Amman, a group of 20 students from Amman enrolled in the Faculty of Foreign Languages at the University of Jordan were asked to fill a questionnaire. Results: The study has found out that phonological instability characterizes some phonemes. This instability can be explained by the alternation that affects certain consonants and vowels, and this alteration can be attributed to several linguistic and social reasons. The study also observes that at the morphosyntactic level, loanwords are classified into three categories based on pluralization. On the other hand, and at the morphological level, some loanwords have received complete morphological integration while others are only partially integrated. Conclusions: The study concludes that loanwords occur in monolingual speech and follow the linguistic patterns of Jordanian Arabic of Amman. Their users are often unaware of their foreignness. Accordingly, French loanwords in Jordanian Arabic can be considered as borrowings rather than code-switching since they follow the system of Jordanian Arabic of Amman rather than the one of the French language..